2006
DOI: 10.1016/s1028-4559(09)60205-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Growth-, Angiogenesis- and Invasion-Related Factors in The Development of Placenta Accreta

Abstract: Placenta accreta is the major cause of maternal death complicated by massive peripartum hemorrhage. Its development is traditionally considered to be related to a decidual defect caused by previous cesarean deliveries or uterine curettages. Usually, placental villi firmly adhere to the superficial myometrium and deeply invade, or even penetrate, the uterine wall. Abnormal uteroplacental neovascularization is another characteristic. Therefore, we hypothesized that placenta accreta develops as a result of abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 72 publications
0
31
1
1
Order By: Relevance
“…9 Tseng and Chou hypothesized that the abnormal expression of growth, angiogenesis, and invasionrelated factors in the trophoblast populations are the main factors responsible for the occurrence of placenta accreta. 9 In addition, Cohen et al reported that the cytotrophoblast secretes factors that favor invasion, whereas decidua seems to not have a major role in regulating cytotrophoblast invasion in vitro. 10 Data from Tantbirojn et al explained invasion of larger vessels in the outer myometrium and near the serosa to be determined by access rather than a preexisting defect in trophoblastic growth that would produce uncontrolled invasion through the entire depth of the myometrium in cases of accreta.…”
Section: Discussionmentioning
confidence: 99%
“…9 Tseng and Chou hypothesized that the abnormal expression of growth, angiogenesis, and invasionrelated factors in the trophoblast populations are the main factors responsible for the occurrence of placenta accreta. 9 In addition, Cohen et al reported that the cytotrophoblast secretes factors that favor invasion, whereas decidua seems to not have a major role in regulating cytotrophoblast invasion in vitro. 10 Data from Tantbirojn et al explained invasion of larger vessels in the outer myometrium and near the serosa to be determined by access rather than a preexisting defect in trophoblastic growth that would produce uncontrolled invasion through the entire depth of the myometrium in cases of accreta.…”
Section: Discussionmentioning
confidence: 99%
“…Without a normal decidual plate and Nitabuch’s layer, the villous trophoblast has direct access to the maternal myometrium. Tseng et al theorize that trophoblastic migration and invasion during normal placental development must be interdependently influenced by different kinds of molecules such as growth factors and their receptors, cytokines, hormones, adhesion molecules and enzymes in an autocrine or paracrine manner and that normal placentas do not proceed beyond the inner third of the myometrium through tight spatial and temporal regulation (27). The role of decidua in preventing abnormal placentation is probably by a autocrine/paracrine feedback.…”
Section: Etiologymentioning
confidence: 99%
“…This finding may be focal in some cases while the decidua is present in areas adjacent to the foci of accreta. This decidual maldevelopment in placenta accreta is usually associated with previous instrumentation as in the case of prior cesarean sections or uterine curettages [27]. …”
Section: Pathogenesismentioning
confidence: 99%